An In-depth Study of the Implementation of Hindi Language Curriculum at Upper Primary Stage - Sadayat, Chandra (INDIAN EDUCATIONAL REVIEW, 2017)
Hindi language education in India is large and diverse in terms of its size, place and role of the language. Besides being the official language of the country, Hindi is spoken by the largest number of people in the country and serves as a medium of instruction in schools. It is taught as a first, second and third language in different school systems. Curriculum development and materials for teaching-learning of Hindi at school level is carried out at various levels. The National Curriculum Frameworks developed at the national level serve as a model curriculum for the States/UTs while the states have freedom to adopt, adapt or develop their own curriculum. The recent curricular revision in India, National Curriculum Framework (NCF–2005) (NCERT, 2005), provides guidelines for marching towards the goal of quality education for all children in school. In its call for the spread of equitable quality education, the NCF–2005 stresses the need for a paradigm shift in the way of planning and implementation of various aspects of education (which includes teaching-learning, assessment and other activities in and outside school). The Position Paper on Teaching of Indian Languages by the National Focus Group (NCERT, 2005) deliberated on the problems and issues of teaching of Indian languages in the multilingual contexts, besides suggesting methods and strategies for improving the quality of language teaching in the variety of teaching situations that exists today. There exist varieties of language teaching situations in India depending upon the teachers’ language proficiency and pedagogical knowledge, language environment, resources for teaching learning of the language, and so on.